Approaches to ab initio molecular replacement of α‐helical transmembrane proteins. Issue 12 (4th December 2017) - Thomas, Jens M. H.; Simkovic, Felix; Keegan, Ronan; Mayans, Olga; Zhang, Chengxin; Zhang, Yang; Rigden, Daniel J.
Abstract : Homology‐independent methods for ab initio phasing of α‐helical transmembrane proteins are explored. Abstract : α‐Helical transmembrane proteins are a ubiquitous and important class of proteins, but present difficulties for crystallographic structure solution. Here, the effectiveness of the AMPLE molecular replacement pipeline in solving α‐helical transmembrane‐protein structures is assessed using a small library of eight ideal helices, as well as search models derived from ab initio models generated both with and without evolutionary contact information. The ideal helices prove to be surprisingly effective at solving higher resolution structures, but ab initio ‐derived search models are able to solve structures that could not be solved with the ideal helices. The addition of evolutionary contact information results in a marked improvement in the modelling and makes additional solutions possible.